Ptsn/go co-catalyst for quasi-solid-state dye sensitized solar cells - Voranuch Somsongkul (2018)
© 2018 Trans Tech Publications, Switzerland. Dye sensitized solar cells (DSSCs) consist of photoanodes (dye adsorbed porous semiconductor film), electrolytes and counter electrodes. Nanostructured materials play important parts in both the photoanodes and the counter electrodes, while dyes are there to absorb photons and generate electron-hole pairs and electrolytes are there to transfer electrons from the photoanodes to the counter electrodes. In this study, to enhance light absorption and minimize electron-hole recombination, Ag nanoparticles and MgO nanolayer were coated on TiO2, respectively. To enable a long lifetime, i.e. avoiding liquid electrolyte leakage, quasi-solid-state (QSS) DSSCs were fabricated. PtSn nanoparticles were prepared by a simple chemical reduction method on graphene oxide (GO) to compare with conventional Pt catalyst on FTO substrates as counter electrodes. An average efficiency of the QSS DSSCs with PtSn/GO co-catalysts was found to outperform that of the QSS DSSCs with conventional Pt catalyst. A mixed microstructure of the PtSn/GO co-catalyst was observed. Although, PtSn2 and Pt2 Sn3 phases were suggested by XRD, in a small region observed by EDX-STEM, it was found that C, O and Si were distributed uniformly on the graphene oxide film. Pt was also distributed uniformly, but the signal was low so there were only a few X-Ray counts across the image. There was no sign of Pt being concentrated in the particles. However, Sn was found to be concentrated in the particles without any other elements.